Meta-analysis of single-case treatment effects on self-injurious behavior for individuals with autism and intellectual disabilities. (February 2017) - Morano, Stephanie; Ruiz, Salvador; Hwang, Jiwon; Wertalik, Jennifer L.; Moeller, Jeremy; Karal, Muhammed Akif; Mulloy, Austin
Background and aim: Research has demonstrated that a variety of treatments can reduce or eliminate self-injurious behavior (SIB) in individuals with autism and/or intellectual disabilities but evidence suggests that not all treatments are equally effective. Methods: We used multi-level meta-analysis to synthesize the results of 137 single-case design studies on SIB treatment for 245 individuals with autism and/or intellectual disabilities. Analyses compare the effects of various behavioral and medical treatments for SIB and assess associations between treatment effects and participant- and study-level variables. Results: Findings suggest differential reinforcement, punishment, and treatment packages with reinforcement and punishment components resulted in the largest SIB reductions. Conclusions: Results indicate that overall, treatment for SIB is highly effective and that participant and study characteristics do not moderate treatment effects. Implications: Based on results and in line with current practice recommendations, we encourage use of reinforcement-based procedures in all cases of SIB. In the event that reinforcement-only treatments have failed or if SIB poses a serious, immediate threat to the health and well-being of an individual, our results suggest that overcorrection paired with reinforcement may be the most effective as well as less invasive alternative.